Factors influencing the microbial composition of human milk - Mantziari Anastasia; Rautava Samuli (Elsevier, 2022)
Aside from nutritional components, human milk is rich in microorganisms. Through breastfeeding these microorganisms are introduced to the infant gut where they may transiently or persistently colonize it. Therefore, the human milk microbiota may be an important factor which shapes the infant gut microbiota further influencing infant health and disease. In the current review we aim to give a brief updated insight into the putative origin of the human milk microbiota, its constituents and the possible factors that shape it. Understanding the factors that determine the human milk microbiota composition and function will aid developing optimal postnatal feeding and intervention strategies to reduce the risk of communicable and noncommunicable diseases.